Prediction of Generalized Anxiety Disorder Based on Self-Handicapping with the Mediating Role of Worry - SeyedEbrahimi, Seyed Aliasghar; SeyedEbrahimi, Seyed Alireza; Firouzi, Manijeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The objective of this study was to examine whether self-handicapping predicts generalized anxiety disorder (GAD) symptoms and to investigate the mediating role of worry in this relationship. Methods and Materials: This descriptive-correlational study was conducted among 395 young adults in Tehran, selected through stratified random sampling based on the Morgan and Krejcie sample size table. Participants completed standardized self-report instruments including the Self-Handicapping Scale (SHS), the Penn State Worry Questionnaire (PSWQ), and the Generalized Anxiety Disorder 7-item Scale (GAD-7). Data were analyzed using SPSS-27 for descriptive and correlational statistics, and AMOS-21 for structural equation modeling (SEM). Model fit indices and standardized path coefficients were used to evaluate the adequacy of the proposed mediation model. Findings: Results revealed that self-handicapping was significantly and positively correlated with both worry (r = .57, p < .001) and GAD symptoms (r = .49, p < .001). Worry was also strongly associated with GAD symptoms (r = .61, p < .001). SEM analysis showed good model fit (χ²/df = 2.35, RMSEA = 0.058, CFI = 0.96, TLI = 0.95). Path analysis indicated that self-handicapping had a significant direct effect on GAD (β = 0.28, p < .001), a significant indirect effect through worry (β = 0.30, p < .001), and a substantial total effect (β = 0.58, p < .001), confirming worry as a partial mediator. Conclusion: Targeting both self-handicapping and worry in preventive and therapeutic interventions may enhance the effectiveness of anxiety disorder treatments, especially in performance-oriented and culturally collectivist contexts.